Aproximación Al Discurso de la Acogida y la Solidaridad en Torno al Rescate Del Buque Aquarius en Una Muestra de la Prensa Española - Dra. María MARTÍNEZ LIROLA (Fonseca, Journal of Communication, 2023)
This study will analyse the main linguistic characteristics of a news sample in order to deepen on the discourses that the Spanish press presents regarding the humanitarian aid that Spain offered to host the Aquarius ship in 2018. This article offers a critical analysis of the discourse of hospitality and solidarity that is generated in the Spanish press regarding the rescue of the Aquarius ship and it deepens on the “we-they” binomial.